DIGITALISASI PEMERINTAHAN NAGARI MELALUI IMPLEMENTASI SISTEM INFORMASI MANAJEMEN NAGARI DI NAGARI KAMANG MUDIAK KABUPATEN AGAM - Asniati Bahari; Devi Yulia Rahmi; Jefril Rahmadoni; Khairil Anwar; Alfin Adha Anshar (Jurnal Hilirisasi IPTEKS, 2023)
Indonesia's vision for 2025 is to become an advanced knowledge-based society. This can be achieved by implementing e-government or digitizing government, from the central government down to the lowest level of government, namely the village administration. However, not all Nagari in West Sumatra can operate and serve the population optimally due to limitations in producing transparent and timely information. This activity aims to implement the digitalization of the Nagari Government using the website-based Nagari Management Information System (SIMNag). This activity is in collaboration with the Wali Nagari Kamang Mudiak. The implementation method is through a lecture approach, practice, and question and answer. Participants in the SIMNag socialization activity involved the Wali Nagari, Wali Jorong, Nagari officials, and residents of Nagari Kamang Mudiak. The activity was carried out at the Wali Nagari Kamang Mudiak Office, District. Kamang Magek, Regency. Religion. The result of this activity is the creation of a Nagari Kamang Mudiak Nagari Information System (SIMNag), which is helpful for the Nagari Government in five stages of E-Government by providing Nagari Profile information, facilitating two-way communication between Residents and Migrants; integration between residents and Nagari apparatus through the Nagari Tageh menu; residents and migrants can update their data; community participation for the progress of the Nagari through the complaint and aspiration system menu. SIMNag is also equipped with electronic mail and electronic archives.